Preliminary Evaluation of Alkali–Glycine Pretreatment for Base Metal Leaching from Waste Printed Circuit Boards (PCB) - Agita Kaila Warohmah; Yus Rama Denny; Ganesha Antarnusa; Mochamad Reza Firdaus (SEARCH: Science Education Research Journal, 2026)
Waste printed circuit boards (PCB) have potential as a secondary source of valuable metals; however, the high content of base metals may hinder the recovery of precious metals, thereby requiring a pretreatment stage. This study aimed to conduct a preliminary evaluation of alkali–glycine pretreatment for base metal leaching from waste printed circuit boards. PCB samples were reduced to a particle size of <2 mm and separated into particle size fractions of −60 mesh and −120 mesh. The pretreatment stage was carried out under alkaline conditions, followed by glycine leaching using a glycine concentration of 30 g/L at pH 11, agitation speed of 300 rpm, and leaching time of 24 h under ambient conditions. Initial characterization was performed using X-Ray Fluorescence (XRF) and Inductively Coupled Plasma (ICP), while leaching filtrates were analyzed using Atomic Absorption Spectroscopy (AAS). The characterization results showed that Cu was the dominant metal with a concentration of 21.775 wt.%, while Au and Ag contents reached 522 ppm and 668 ppm, respectively. Leaching results indicated that Cu and Zn were dissolved in limited amounts, whereas Au was not detected in the filtrate. Cu recovery remained relatively low and showed no significant difference between particle sizes, indicating that particle size reduction under the applied conditions had limited influence on leaching performance. The findings suggest that alkali–glycine pretreatment has potential as an initial step for reducing base metal content prior to precious metal recovery, although further optimization of operating conditions is required to improve leaching efficiency.